Design of Air Pollution Measurement Detection Using Microcontroller NodeMCU ESP 8266 Based on IoT - Yudi Irawan Chandra; Fitri Sjafrina; Diyah Rury Irawati; Marti Riastuti; Winda Sari Br. Purba (IJISTECH (International Journal of Information System and Technology), 2022)
The East Jakarta area has many residential areas, from the lower to the upper classes, and residential areas for businesses such as malls, markets, mini supermarkets, and protected tourist attractions, for example, the urban forest area. East Jakarta City is currently trying to maintain the excellent air quality in the area. Currently, the local government's prevention of poor air quality and air quality checks in East Jakarta is not going well because the budget requires a large amount of money. Therefore, a tool was made to detect air quality. The tool built in this study is based on the MQ-135, DHT-11, NodeMCU 8266 microcontroller, and Blynk application using the C++ language on the Arduino application. This tool is expected to provide information to users regarding the level of air quality in the area. This tool will automatically connect to an available wifi network. An air quality notification will immediately appear, along with the temperature and humidity values displayed on the smartphone. The tool made is expected to help view air quality. All information obtained can be helpful for follow-up by the government and the community to maintain the beauty and good air quality in the area